Longitudinal Trend of Plasma Concentrations of Extracellular Vesicles in Patients Hospitalized for COVID-19 - Campello, Elena; Radu, Claudia Maria; Simion, Chiara; Spiezia, Luca; Bulato, Cristiana; Gavasso, Sabrina; Tormene, Daniela; Perin, Nicola; Turatti, Giacomo; Simioni, Paolo (Frontiers in Cell and Developmental Biology, 2022)
Plasma concentrations of extracellular vesicles (EVs) originating from cells involved in COVID-19-associated coagulopathy (CAC), their longitudinal trend and association with clinical outcomes were evaluated. Blood samples of consecutive COVID-19 patients admitted to a medical Unit were longitudinally collected within 48 hours of admission, at discharge and 30 days post-discharge. EVs were analyzed using high sensitivity flow cytometry and phospholipid-dependent clotting time (PPL). The following EVs were measured: endothelium-, platelet-, leukocyte-derived, bearing tissue factor (TF)+, angiotensin-converting enzyme (ACE2)+, platelet-derived growth factor receptor-β (PDGF-β)+ and SARS-CoV-2-nucleoprotein (NP)+. 91 patients were recruited for baseline EV analysis (mean age 67 ± 14 years, 50.5% male) and 48 underwent the longitudinal evaluation. From baseline to 30-day post-discharge, we observed significantly decreased plasma concentrations of endothelium-derived EVs (E-Selectin+), endothelium-derived bearing TF (E-Selectin+TF+), endothelium-derived bearing ACE2 (E-Selectin+ACE2+) and leukocyte-EVs bearing TF (CD45+TF+), p<0.001, p=0.03, p=0.001, p=0.001, respectively. Conversely, platelet-derived (P-Selectin+) and leukocyte-derived EVs (CD45+) increased from baseline to 30-day post-discharge (p= 0.038 and 0.032, respectively). EVs TF+, ACE2+, PDGF-β+ and SARS-CoV-2-NP+ did not significantly change during the monitoring. PPL increased from baseline to 30-day post-discharge (+6.3 sec, p=0.006). P-Selectin+EVs >1054/µL were associated with thrombosis (p=0.024), E-Selectin+EVs ≤531/µL with worsening/death (p 0.026) and 30-day P-Selectin+ and CD45+EVs with persistent symptoms (p<0.0001). We confirmed increased EVs originating from cells involved in CAC at admission and discharge. EVs derived from activated pericytes and expressing SARS-CoV-2-NP were also detected. 30-day post-discharge, endothelium-EVs decreased, while platelet- and leukocyte-EVs further increased, indicating that cellular activation persists long after the acute phase.